Hubungan Pendidikan Dan Hukum Dalam Upaya Peningkatan Kompetensi Guru - Rosmawiah Rosmawiah; Yossita Wisman; Marni Marni (Jurnal Ilmiah Kanderang Tingang, 2022)
This paper aims to discuss the relationship between education and law and its position in Indonesian society. The education situation in Indonesia is implemented and must be enforced appropriately in accordance with applicable laws and regulations. All teachers must understand that the concept or method of education is always evolving in accordance with applicable laws and regulations. The point is we have to understand, practice with the present context. Likewise, the law must be applied in the present context. In everyday life, humans must walk, not stop, turn left and right, sometimes backwards, but must continue to advance in achieving what they want by paying attention to their surroundings, one of which is paying attention to related matters. for education and law. Epistemologically, axiologically and ontologically what is meant by education? What is the legal basis for education in Indonesia? How is the relationship between education and law in an effort to increase teacher competence?